Counterfeit alcohol distribution: A criminological script network analysis. (July 2020) - Bellotti, Elisa; Spencer, Jon; Lord, Nick; Benson, Katie
This paper analyses a series of subsequent and connected investigations by a domestic European regulator on the network of distribution of counterfeit alcohol across two jurisdictions. The analysis mixes script analysis, a narrative framework for enhancing the understanding of how crimes unfold and are organized, with multi-node multi-link social network analysis, to observe the social structure in which crime scripts take place. We focus our attention on the key players that occupy strategic positions within the network of the crime commission process, from where they overview and control the various phases (scenes) and perform brokerage activities across the scenes, and on strategies of concealment of illicit products beyond the facade of legitimate business. Our findings indicate that actors in charge of managing the proceeds of the criminal activity are also the ones better positioned to monitor the entire process. The overall structure of the criminal network shows a good level of resilience and efficiency, although actors do not adopt common traits of a criminal lifestyle that facilitate secrecy and covertness. We believe that, by shifting the analysis from the nature of the group organization to the network of links between all the aspects of a crime commission process, the organizational structure and its weakest links become more detectable, easier to compare across proto- and meta-scripts, and ultimately more prone to situational preventive measures.